Pasture Cows Nutrition in Submounteens Condition in Sumava Region - Lenka Martínková; Bohuslav Čermák; Barbora Vondrášková; Miloslav Šoch; Luboš Zábranský; Jan Frelich; Miroslav Maršálek (Scientific Papers Animal Science and Biotechnologies, 2023)
Quality of meadow and grazing herbage was evaluated. Dry matter, crude protein, ash, fat and fibers were analyzed. Herbage sampling was realized on three pastures of cattle with higher altitudes. Grass and herbage are the most natural and optimal feedstuff for cattle in fresh and as silage feed. Grazing management should notably regulate the pasture composition, i.e. support dominance of soft stoloniserous strains of grasses and decrease occurrence of weed and less value strain of gramineous grasses. The impact of grazing on milk performance and health of dairy cows was surveyed on sub-mountain farms. The higher milk, fat and protein yields were found in grazing season in comparison with winter confinement period.